12th Russia/CIS/Baltic/Japan Symposium on Ferroelectricity and 9th International Conference on Functional Materials and Nanotechnologies (RCBJSF–2014–FM&NT). Issue 1 (9th March 2015) - Sternberg, Andris; Grinberga, Liga; Sarakovskis, Anatolijs; Rutkis, Martins
Abstract : The joint International SymposiumRCBJSF–2014–FM&NT successfully has united two international events – 12th Russia/CIS/Baltic/Japan Symposium on Ferroelectricity (RCBJSF-12 ) and 9th International Conference Functional Materials and Nanotechnologies (FM&NT-2014 ). TheRCBJSF symposium is a continuation of series of meetings on ferroelectricity, the first of which took place in Novosibirsk (USSR) in 1976.FM&NT conferences started in 2006 and have been organized by Institute of Solid State Physics, University of Latvia in Riga. In 2012 the International program committee decided to transform this conference into a traveling Baltic State conference and the FM&NT-2013 was organized by the Institute of Physics, University of Tartu, Estonia. In 2014 the joint international symposiumRCBJSF–2014–FM&NT was organized by the Institute of Solid State Physics, University of Latvia and was part of Riga – 2014, the European Capital of Culture event. The purpose of the joint Symposium was to bring together scientists, students and high-level experts in solid state physics, materials science, engineering and related disciplines. The number of the registered participants from 26 countries was over 350. During the Symposium 128 high quality scientific talks (5 plenary, 42 invited, 81 oral) and over 215 posters were presented. All presentations were divided into 4 parallel sessions according to 4 main topics of the Symposium: Ferroelectricity, including ferroelectrics and multiferroics, pyroelectrics, piezoelectrics and actuators, integrated ferroelectrics, relaxors, phase transitions and critical phenomena. Multifunctional Materials, including theory, multiscale and multiphenomenal material modeling and simulation, advanced inorganic, organic and hybrid materials. Nanotechnologies, including progressive methods, technologies and design for production, investigation of nano- particles, composites, structures, thin films and coatings. Energy, including perspective materials and technologies for renewable and hydrogen energy, fuel cells, photovoltaics, LEDs, OLEDs. Based on these reports, 48 papers are included in this volume of IOP Conference Series: Materials Science and Engineering . Additional information aboutRCBJSF–2014–FM&NT is available at the homepagehttp://www.fmnt.lu.lv . The Organizing Committee would like to thank all the speakers, contributors, session chairs, referees and other involved staff for their efforts in making theRCBJSF–2014–FM&NT successful. Sincerely, organizers of the event Andris Sternberg Liga Grinberga Anatolijs Sarakovskis Martins Rutkis